ANALISIS KEKUATAN POROS DAN RODA BERSIRIP PADA ALAT PENANAM PADI PORTABEL MELALUI PENDEKATAN SIMULASI - Ragil Sukarno; I Wayan Sugita; Ahmad Hartono (Universitas Negeri Jakarta, 2022)
Farmers need automatic rice planting tools to increase crop yields. Currently, automatic planting tools are already on the market, but the price is relatively high, so an alternative automatic rice planter tool is needed that has a more affordable price. One of the very important components in an automatic rice planter is the shaft and wheels, so in this study focused on these two components. This study aimed to determine the strength of the shaft and finned wheels on the planter in the jajar legowo system through a simulation approach. This research method uses a simulation approach using Autodesk Inventor software which is applied to the components of the shaft and the wheel of the rice planter. The research begins with making a 3D model design, determining the shaft and wheel materials, meshing, determining boundary conditions, determining the loading position, and then running a voltage analysis simulation. The shaft material used is JIS G4501 Grade S45C steel, while the material for the wheels is JIS G3101 Grade S400 steel. The simulation results showed that the maximum von mises stress was 54.90 MPa, the maximum displacement was 0.113 mm, and the minimum safety factor value of 3.8. These results show that the shaft and wheel design on the rice planter has met the safe limit and can be continued in the manufacturing process stage.